UNRI Kukerta Service in Gunung Sari Village: Geospatial-Based Mapping in Gunung Sari Village - Muhd. Arief Al Husaini; Ade Rizka; Dhea Rahmazani; Dian Andarini; Dika Junanda; Khairul Amar; Nico Stefanus Sembiring; Nuraini Meltari; Siti Maysari; Syahdia Maharani; Ummu Salamah Hasibuan (Indonesian Journal of Advanced Social Works, 2023)
Gunung Sari is one of the villages that exist in the sub-district of Gunung Sahilan, Kampar Regency, Riau province, Indonesia. Commodities that can be obtained are the result of plantations in the form of rubber sap and palm fruit. This village is listed in the list of 100 best villages according to Province and Regency in Indonesia in 2018 issued by the Ministry of Village, Development of Left Regions and Transmigration. The distance traveled to the village of Gunung Sari is 120 km from the city of the new week, with two hours using the car. The purpose of community devotion is mapping villages as a basis in the development of the area of Gunung Sari Village, Gunung Sahilan District. Image shown on the map of the village gives an overview of land cover in Gunung Sari Village. Therefore, presentation of the map needs to be done with the passage of time to adjust the latest conditions in Gunung Sari Village. In planning development, the map is used as an analysis material of the region by paying attention to land cover. In addition, the level of plantation density can be used as an analysis material for development planning in the form of public facilities that can be utilized by the community. Gunung Sari village is dominated by palm plantations, only a few settlements are available. Land Diversion for green open space can be planned by utilizing the map.